Degradation Characteristics of Aniline with Ozonation and Subsequent Treatment Analysis. (6th September 2015) - Jing, Zhaoqian; Cao, Shiwei; Yu, Ting; Hu, Jing
Abstract : Owing to the toxicity and low biodegradability of aniline in water, its removal usually needs high cost processes such as adsorption and advanced oxidation. The degradation characteristics of aniline during ozonation were studied. The influence of operation parameters such as contact time, initial concentration, ozone dosage, temperature, and pH was also investigated. With ozone dosage of 22 mg/L, neutral pH, and room temperature, the ozonation removed aniline efficiently. After two hours' ozonation, aniline removal reached 93.57%, and the corresponding COD removal was 31.03%, which indicated most of aniline was transformed into intermediates. At alkaline conditions, the aniline was more susceptible to being removed by ozonation owing to more hydroxyl radicals' production. The results of GC-MS indicated many intermediates appeared during the process of ozonation such as butane diacid, oxalic acid, and formic acid. The intermediates produced during ozonation were more biodegradable than aniline; thus the ozonation of such organic compounds as aniline could be integrated with biological processes for further removal.